2016
DOI: 10.1001/jamasurg.2016.1662
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Enoxaparin Dosage Adjusted by Anti–Factor Xa Trough Level and Clinically Evident Venous Thromboembolism After Trauma

Abstract: In this study, subprophylactic anti-Xa trough levels were common in trauma patients. Enoxaparin dosage adjustment may lead to a reduced rate of VTE without an increased risk of bleeding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
208
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 126 publications
(217 citation statements)
references
References 28 publications
7
208
1
1
Order By: Relevance
“…Indeed studies have suggested that weight-adjusted dosing of PP is important in order to achieve therapeutic levels of antifactor Xa [27]. Dosing of PP guided by anti-Xa measurements has been shown to reduce the incidence of DVT without increasing bleeding rates [28].…”
Section: Relationship With Previous Studiesmentioning
confidence: 99%
“…Indeed studies have suggested that weight-adjusted dosing of PP is important in order to achieve therapeutic levels of antifactor Xa [27]. Dosing of PP guided by anti-Xa measurements has been shown to reduce the incidence of DVT without increasing bleeding rates [28].…”
Section: Relationship With Previous Studiesmentioning
confidence: 99%
“…Currently, it is not standard practice in ANZ to measure anti-Xa activity in patients receiving prophylactic LMWH. However, existing data suggest dose adjustment based on peak anti-Xa levels, may reduce the incidence of deep vein thrombosis (DVT) [12][13][14][15][16] .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, higher empirical dosing (e.g. 30 mg SC enoxaparin BD) may still provide inadequate chemoprophylaxis in many patients, as evidenced by low anti-Xa activity and the development of VTE [12][13][14][15]17,18] .…”
Section: Introductionmentioning
confidence: 99%
“…13 Inadequate aFXa levels in surgical patients who receive enoxaparin prophylaxis have similarly been associated with symptomatic VTE in plastic surgery and trauma surgery patients and with all-cause VTE in the trauma and orthopaedic populations. [20][21][22][23] The heparin doses required to achieve goal prophylactic aFXa levels (8.9-18 units/kg/h) were similar to the starting infusion rate for the acute coronary syndrome protocol at our institution (12 units/kg/h). This may be due to the hypermetabolic nature of patients in the postoperative period.…”
Section: Discussionmentioning
confidence: 99%